Does Your Program Know Its AKI and CRRT Epidemiology? The Case for a Dashboard - Mottes, Theresa A. (Frontiers in Pediatrics, 2020)
Current acute kidney injury (AKI) literature focus on diagnosis, treatment, and outcomes. While little literature exists studying the quality of care delivered to patients with AKI. However, improving outcomes for patients is dependent on the specifics of the delivered care (i.e., the who, what, when, and how). Therefore, it is necessary to direct attention to process measures to assess the relationship between care and outcomes. The application of quality improvement science to the care of AKI, uses a series of metrics encompassing both processes and outcomes to better understand, evaluate and ensure the delivery high quality care.